神经传导速度差异规律量化评估肌萎缩侧索硬化症 - 张俊; 樊东升; 郑菊阳; 康德瑄 (中国临床康复, 2004)
背景:肌电图的神经传导速度异常是肌萎缩侧索硬化( amyotrophic lateral sclerosis,ALS)的诊断标准之一,可否以其变化差异规律来量化患者病情变化和评估预后? 目的:研究肌萎缩侧索硬化 (amyotrophic lateral sclerosis,ALS)患者中神经传导速度的改变,建立量化评定肌萎缩侧索硬化病情及其预后的神经生理指数. 设计:回顾性分析. 地点和对象:本研究的地点为北京大学第三医院神经科,研究对象为北京大学第三医院神经内科 1997-02/1999-03住院患者. 方法:对 21名 ALS患者的 30条尺神经、 32条正中神经及 24名健康对照组的 38条尺神经、 40条正中神经进行运动传导速度 (motor conduction velocity, MCV)及感觉传导速度( sensory conduction velocity, SCV)和 F波进行检测.两组间数据进行统计学分析. 主要观察指标:两组正中神经神经传导速度与 F波, ALS组患者小指展肌的肌力与 CMAP波幅 /DML× F出现率数值的相关性. 结果: ALS组正中神经、尺神经运动传导速度的远端潜伏期 (distal motor latency, DML)、肌肉动作电位( compound muscle action potential, CMAP)波幅及面积、 F波的出现率较对照组有显著性差异.而两组 MCV、 SCV、 F波的潜伏期差异无显著性. ALS组中 10名小指展肌的肌力与 CMAP波幅 /DML× F出现率的数值有显著的相关性 (r=0.89,P< 0.01). 结论: CMAP波幅 /DML× F波的出现率是一种有效的客观的电生理指数,可对 ALS病情及其预后进行量化评估. BACKGROUND:Nerve conductive velocity plays a critical role in the diagnosis of amyotrophic lateral sclerosis(ALS),so as to exclude similar axonal or demyelinating neuropathy.We want to find a way quantitatively to evaluate sequential changes in the course of ALS by studying neuroelectrophysiological abnormalities. OBJECTIVE:To study nerve conduction velocity in ALS patients and set up a standardized neurophysiological assessing index. DESIGN:A retrospective analysis. SETTING and PARTICIPANTS:Twenty-one in-patients with ALS and 24 normal controls were recruited in the Department of Neurology,the Third Affiliated Hospital of Beijing University. INTERVENTIONS:Motor conduction velocity(MCV),sensory conduction velocity(SCV) and F-wave were studied in 30 ulnar nerves and 32 median nerves of 21 ALS patients.Thirty-eight ulnar nerves and 40 median nerves of 24 normal subjects matched for age,gender and height served as controls.Statistical analysis was conducted in comparison of data between the two groups. MAIN OUTCOME MEASURES:The correlation between the bilateral median nerve conduction velocity and F wave,and between muscle strength of abductor digiti minimi and the frequency of 〖 the amplitude of the compound muscle action potential(CMAP)/distal motor latency(DML)]× F were detected. RESULTS:There was significant difference in the neurophysiological data of median and ulnar nerves between ALS and control groups,including reduced CMAP and area,prolonged DML and F frequency.MCV,SCV and latency of F-wave were normal.An ALS neurophysiology index was derived from nerve conduction studies and consisted of the expression of(CMAP amplitude/DML)× F frequency.This index was strongly correlated with ADM muscle power in 10 ALS patients(r=0.89,P< 0.01). CONCLUSION:(CMAP amplitude/DML)× F frequency is an effective neurophysiology index and could be used to quantify abnormality in ALS. 0 7 1380-1381 8